RAPID VERIFICATION OF VIRUS PARTICLE PRODUCTION FOR A PERSONALIZED VACCINE - JONES, Frank R; NIAZI, Kayvan; RICE, Adrian E (2019)
Methods for rapidly confirming production of infectious viral vectors, for use in clinical grade personalized neo-antigen vaccines for subjects in need thereof, are provided. L'invention concerne des méthodes de confirmation rapide de la production de vecteurs viraux infectieux, destinés à être utilisés dans des vaccins néo-antigènes personnalisés de qualité clinique destinés à des sujets nécessitant ces derniers.